The Characteristic of Taro Flour Based Pasta with Addition of Modified Starch and Hydrocolloids - Sonia Sonia; Elisa Julianti; Ridwansyah Ridwansyah (Indonesian Food and Nutrition Progress, 2019)
A way to make people with coeliac disease able to eat a gluten-based food is by creating gluten-free food like taro flour based pasta with the addition of modified starches and hydrocolloids. In this research, the pasta were made by using the heat moisture treatment of modified starch of banana and potato were combined with taro flour with the proportion 0%:30%:70%, 7.5%:22.5%:70%, 15%:15%:70%, 22.5%:7.5%:70% and 30%:0%:70% and added with 0,5% of hydrocolloids such as xanthan gum, carboxyl methyl cellulose (CMC) and arabic gum. The results showed that the proportions of starches and flour were highly significantly different (p < 0.01) in protein content, cooking time, elongation and significantly different (p < 0.05) in crude fibre content. The influence of hydrocolloids addition was found to be highly significantly different (p < 0.01) in cooking loss, elongation; and significantly different (p < 0.05) in cooking time. The interactions of proportions of starches and flour and the addition of hydrocolloids were highly significantly different (p < 0.01) in crude fibre content, cooking time and elongation. The best spaghetti composition was based on cooking time, cooking loss, and elongation which could be found in the proportion of 15%:15%:70% of modified banana starch, modified potato starch, and taro flour with the addition of xanthan gum of 0.5%.